Successive Synthesis of Well-Defined Star-Branched Polymers by Iterative Methodology Based on Living Anionic Polymerization - Hirao, Akira; Inoue, Kyouichi; Higashihara, Tomoya; Hayashi, Mayumi (Polymer journal, 2008)
The subject of this review is to introduce a novel iterative methodology based on living anionic polymerization using specially designed 1,1-diphenylethylene (DPE) derivatives recently developed for the synthesis of well-defined many armed star-branched polymers with same or chemically different arm segments. The methodology basically involves only two sets of the following reaction conditions for the entire iterative synthetic sequence: (a) a linking reaction of a living anionic polymer with a DPE-chain-functionalized polymer, and (b) an in situ reaction of a DPE-functionalized agent with the anion generated by the linking reaction to reintroduce the DPE functionality usable for the next reaction. The number of arms to be linked by each stage of the iteration depends on the starting core and DPE-functionalized agents and can dramatically increase by the agent of choice. New functional asymmetric star-branched polymers involving conductive and rigid rod-like poly(acetylene) segment(s) have been synthesized by the methodology using the intermediate polymer anions produced by the linking reaction as macroinitiators to polymerize 4-methylphenyl vinyl sulfoxide, followed by thermal treatment of the resulting star-branched polymers.